A STUDY OF UNILATERAL RETALIATION IN INTERNATIONAL TRADE LAW: AN ANALYSIS OF THE UNITED STATES VS CHINA DISPUTE - Kahfi Rasman; Muh Risnain (Department of Law, Faculty of Law, University of Mataram, 2026)
This research analyzes the conformity of unilateral retaliation measures in the trade dispute between the United States (US) and the People’s Republic of China (PRC), particularly through the imposition of additional tariffs during section 301 the 2017–2020 period and the development of reciprocal tariffs in 2025. The study is based on three core principles of the World Trade Organization (WTO) framework: the Most-Favoured-Nation (MFN) principle under Article I:1 of GATT 1994, the commitment to bound tariffs under Article II of GATT 1994, and the rules governing retaliation and the prohibition of unilateral action under Articles 22–23 of the Dispute Settlement Understanding (DSU). The US–China dispute is used as a doctrinal reference to identify elements of violations of MFN and bound tariff obligations, as well as to explain enforcement challenges arising from the inability to finalize panel reports following the Appellate Body crisis since 2019. Employing normative legal research methods with statutory and conceptual approaches, this study argues that tariffs imposed under Section 301 and reciprocal tariffs based on the International Emergency Economic Powers Act (IEEPA) are generally inconsistent with WTO commitments. This is because such measures are discriminatory based on country of origin, may exceed agreed tariff limits, and undermine the DSU framework, which permits retaliation only through multilateral procedures. Furthermore, this research evaluates the effectiveness of the WTO Dispute Settlement Mechanism (DSM) and highlights Article 25 DSU arbitration and the Multi-Party Interim Appeal Arbitration Arrangement (MPIA) as practical alternatives for restoring legal certainty and finality in dispute resolution.